Venous Thromboembolism and Renal Impairment: Insights from the SWIss Venous ThromboEmbolism Registry (SWIVTER) - Spirk, David; Sebastian, Tim; Banyai, Martin; Beer, Jürg H.; Mazzolai, Lucia; Baldi, Thomas; Aujesky, Drahomir; Hayoz, Daniel; Engelberger, Rolf P.; Kaeslin, Thomas; Korte, Wolfgang; Escher, Robert; Husmann, Marc; Mollet, Annette; Szucs, Thomas D.; Kucher, Nils (Seminars in Thrombosis and Hemostasis, 2019)
Renal impairment (RI) has increased substantially over the last decades. In the absence of data from confirmatory research, real-life data on anticoagulation treatment and clinical outcomes of venous thromboembolism (VTE) in patients with RI are needed. In the SWIss Venous ThromboEmbolism Registry (SWIVTER), 2,062 consecutive patients with objectively confirmed VTE were enrolled. In the present analysis, we compared characteristics, initial and maintenance anticoagulation, and adjusted 90-day clinical outcomes of those with (defined as estimated creatinine clearance < 30 mL/min) and without severe RI. Overall, 240 (12%) patients had severe RI; they were older, and more frequently had chronic and acute comorbidities. VTE severity was similar between patients with and without severe RI. Initial anticoagulation in patients with severe RI was more often performed with unfractionated heparin (44 vs. 24%), and less often with low-molecular-weight heparin (LMWH) (52 vs. 61%) and direct oral anticoagulants (DOACs; 4 vs. 12%). Maintenance anticoagulation in patients with severe RI was more frequently managed with vitamin K antagonists (70 vs. 60%) and less frequently with DOAC (12 vs. 21%). Severe RI was associated with increased risk of 90-day mortality (9.2 vs. 4.2%, hazard ratio [HR]: 2.27, 95% confidence interval [CI]: 1.41–3.65), but with similar risk of recurrent VTE (3.3 vs. 2.8%, HR: 1.19, 95% CI: 0.57–2.52) and major bleeding (2.1 vs. 2.0%, HR: 1.05, 95% CI: 0.41–2.68). In patients with severe RI, the use of LMWH versus any other treatment was associated with reduced mortality (HR: 0.37; 95% CI: 0.14–0.94; p = 0.036) and similar rate of major bleeding (HR: 0.59, 95% CI: 0.17–2.00; p = 0.39). Acute or chronic comorbidities rather than VTE severity or recurrence may explain increased early mortality in patients with severe RI. The higher rate of VTE recurrence, specifically fatal events, than major bleeding reinforces the need for effective anticoagulation in VTE patients with severe RI.
Keywords: anticoagulation; mortality; renal impairment; venous thromboembolism